2018
DOI: 10.1371/journal.pone.0196049
|View full text |Cite
|
Sign up to set email alerts
|

The role of SeDeM for characterizing the active substance and polyvinyilpyrrolidone eliminating metastable forms in an oral lyophilizate—A preformulation study

Abstract: A preformulation study of an oral lyophilisate with cetirizine dihydrochloride (CTZ) as active ingredient, mannitol and PVP K30 as bulking agents is presented. CTZ shown a humidity content of 0.150% and a spontaneous hygroscopicity of 0.200% (both determined by SeDeM diagram), demonstrating an adequate stability behavior in solid form. A design of experiments (DoE) performed with both mannitol and PVP K30, followed by a simple factorial design (32) has determined the optimum combination of excipients and CTZ, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 31 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Using the SeDeM-ODT tool the advantages and disadvantages of the powders were established. This tool can be applied to: establish the quantity of excipient needed to obtain a tablet if the active pharmaceutical ingredient (API) does not have a good compressibility profile; observe the differences between the quality of different batches of similar powder; differentiate the excipients that have the same chemical formulation but have different physical properties; differentiate the excipients from the same class (disintegrants, fillers, sweeteners) ( Aguilar-Díaz et al, 2012 , Flórez Borges et al, 2018 , Sipos et al, 2017 , Aguilar-Díaz et al, 2014 , Suñé-Negre et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the SeDeM-ODT tool the advantages and disadvantages of the powders were established. This tool can be applied to: establish the quantity of excipient needed to obtain a tablet if the active pharmaceutical ingredient (API) does not have a good compressibility profile; observe the differences between the quality of different batches of similar powder; differentiate the excipients that have the same chemical formulation but have different physical properties; differentiate the excipients from the same class (disintegrants, fillers, sweeteners) ( Aguilar-Díaz et al, 2012 , Flórez Borges et al, 2018 , Sipos et al, 2017 , Aguilar-Díaz et al, 2014 , Suñé-Negre et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The SeDeM-ODT expert system provides the following advantages in comparison to classical experimental design: the number of excipients required in the final formulation is optimized; a formulation with only one excipient combined with the API – CBD can be obtained; the critical parameters represented by the short disintegration time, compressibility, and mechanical resistance are fulfilled; the decreased time needed to develop a new ODT compared to a classical experimental design where numerous studies were needed to obtain ODTs that accomplished all the critical parameters, especially, disintegration time and compressibility. ( Aguilar-Díaz et al, 2012 , Flórez Borges et al, 2018 , Aguilar-Díaz et al, 2014 , Suñé-Negre et al, 2014 )…”
Section: Introductionmentioning
confidence: 99%
“…Another impact of CMAs relates to process adjustments. Previous studies have demonstrated that PVP can suppress metastable forms of mannitol and eliminate the need for an annealing step in freezing [73].
Fig. 4Ishikawa for process parameters related to the most important quality deviations [44].
…”
Section: Quality Attributes and Related Process/materials Parametersmentioning
confidence: 99%
“…The results show that the new synthesized polythiourea has sufficient rheological properties. Borges, et al [31] used SeDeM Expert System to characterizing the active substance and polyvinyilpyrrolidone eliminating metastable forms in an oral lyophilizate, and the use of SeDeM Diagram provided valuable data regarding the stability behavior of CTZ in its solid form.…”
Section: Pre-formulation Study Of Other Style Tabletsmentioning
confidence: 99%